Notes per a una estilística dels temps verbals - Pérez Saldanya, Manuel (Caplletra. Revista Internacional de Filologia, 2000)
Tenses constitute a complex system of oppositions based on time, aspect, and temporal distance. Taking these oppositions as basic, this article deals with the stylistic properties that verbal tenses acquire in discourse. In addition, it presents an analysis of some stylistically marked uses of the imperfect, the future, the conditional, and the past perfect. In all these cases, the verbal tenses keep some of their basic properties but introduce temporal or aspectual changes thatlead to pragmatic and stylistic changes closely related to certain narrative effects.